Comparison the effect of training of conflict resolution and management of emotional intelligence on Life satisfaction's spouses of war veterans affected psychological disorders - M. Ziakhodadadian; M. Sirati nir; F. Khamseh; A. Ebadi (Afarand Scholarly Publishing Institute, 2012)
Introduction: Warfare makes addition to adverse and psychosomatic disorders on combatants also it puts their families exposed to dangerous and problems. This study performed on object for omparison the effect of training conflict resolution and management of emotional intelligence on life satisfaction's spouses of veterans affected psychological disorders.  Methods and Materials: This is a quazi experimental study of clinical trial type that carried out on 90 veterans spouse in Baqiyatallah hospital (a.s) and Sadr psychiatric center. They were taken by randomization into two intervention groups (conflict resolution and emotional intelligence training) and control group. The education program was developed for conflict resolution group at three sessions in two hours in three weeks and five sessions in two hours in five weeks . However, control group didn't any training. The life satisfaction in three groups determined by Life satisfaction questionnaire at before, and after training (first six weeks after intervention i.e. follow up and second six weeks after intervention i.e. final phase). Results: The results showed that there wasn't significant difference in total mean rank of life satisfaction before intervention between conflict resolution , management of emotional intelligence and case groups (p>0.05) . Also there wasn't a significant difference between three groups after intervention in first six weeks (p<0.05). Whereas There was significant difference between mean rank of life satisfaction in three groups at final phase(p=0.001). Also the Toki test showed that there was significant difference between case group and two other groups (p<0.05) but there wasn't significant difference between conflict resolution and management of emotional intelligence groups. Discussion: Considering the results of this study which explanatory the influence two techniques of intervention on life satisfaction. Therefore it is recommended that be used the conflict resolution skill and management of emotional intelligence programs to promotion the health level and life satisfaction's veterans families.